Presence of Chaperone during Pelvic Examination: Women’s Opinions and Preferences in a Tertiary Hospital in Abakaliki, Ebonyi State, Nigeria - Chidebe Christian Anikwe; CHIADIKOBI JOHN IRECHUKWU; Christian Okechukwu Ogah; Cyril Chijioke Ikeoha; Bartholomew Chukwunonye Okorochukwu; Francis Chigozie Okoroafor; Okechukwu Emmanuel Ndukwe (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Pelvic examination in the evaluation of patients can be a source of dissatisfaction and litigation from patients. A chaperone is beneficial in militating against unforeseen circumstances surrounding this clinical examination. Aim: To access the opinions and preferences of patients in pelvic examinations and factors associated with the use of chaperones in Federal Teaching Hospital Abakaliki, Ebonyi State, Nigeria. Materials and Methods: The present study was a crosssectional study. Women were recruited between October 2017 to April 2018 among patients attending the Gynaecological Clinic at the Federal Teaching Hospital, Abakaliki, Nigeria. A structured questionnaire was used to collect data such as the socio-demographic characteristics, feelings towards pelvic examinations, and preferences about the gender of the examining doctor as well as the presence of a chaperone. Data analysis was done using International Business Machines Statistical Package for the Social Sciences (IBM SPSS) Statistics version 20.0 (IBM Corp., Armonk, NY, USA). Results: Out of 423 questionnaires distributed, 395 respondents completed the survey giving a response rate of 93.4%. The mean age of the respondents were 29.2±6.2 years. Majority of the respondents would prefer to be seen by a female gynaecologist 342 (86.6%). About 50 (12.7%) respondents would decline pelvic examination. The commonest reason given for refusing gynaecologic examination was uncomfortable environment 25 (50%). More than two-third 264 (76.5%) would prefer to have a chaperone present at any pelvic examination. Avoidance of sexual molestation was the commonest reason given for wanting a chaperone to be present 207 (78.4%). Nulliparous women (OR=2.25 95% CI 1.13-4.50) and those with at least a secondary education (OR=7.91 95% CI 4.54-13.78) were also more likely to request a chaperone. Conclusion: Majority of the women in present study wanted the presence of a chaperone during a pelvic examination. It is therefore recommended that chaperones should routinely be offered during pelvic examination in Abakaliki, Ebonyi, Nigeria.